Pengaruh Penyuluhan Kesehatan Terhadap Pengetahuan Masyarakat dalam Penggunaan Obat Golongan Antibiotik - Andi Irdam Hidayat; Ruslan Majid; Asriati Asriati (STIKes Hang Tuah Pekanbaru, 2022)
One of the diseases that is a problem in developing countries is an infectious disease. Along with this, the use of antibiotics cannot be avoided as drugs that are important in the treatment of infections caused by bacteria. On the other hand, the use of antibiotics without a doctor's prescription can lead to antibiotic resistance. Therefore, we need an education and optimization of the community's ability with regard to drug use techniques. The purpose of this study was to analyze the level of public knowledge of using antibiotic class drugs in North Poleang District, Southeast Sulawesi Province. Thus, people need to understand that in health services, antibiotics must be used appropriately and rationally, in order to achieve an effective treatment effect. The research was conducted in North Poleang Subdistrict for two months, from January 2021 to February 2021. This was a quasi experimental study with a one group pre-test or post test study design. The results showed that there was no significant relationship between age and public knowledge in the use of antibiotic class drugs in Poleang Utara District, Bombana Regency the p-value 1,000, there was a significant relationship between the level of education and public knowledge on the use of antibiotic class drugs in Poleang Utara District, Bombana Regency, the p-value = 0,000. There is no a significant relationship between work and public knowledge in the use of antibiotic class drugs in Poleang Utara District, Bombana Regency, the p-value = 0,218, there is a significant effect between counseling on public knowledge in the use of antibiotic class drugs in Poleang Utara District, Bombana Regency, the p-value = 0,000.